2021
DOI: 10.1111/jch.14360
|View full text |Cite
|
Sign up to set email alerts
|

Association of pulsatile stress in childhood with subclinical renal damage in adults: A 30‐year prospective cohort study

Abstract: The pulsatile stress in the microcirculation may contribute to development or progression of chronic kidney disease. However, there is no prospective data confirming whether pulsatile stress in early life affect renal function in middle age. The authors performed a longitudinal analysis of 1738 participants aged 6-15 years at baseline, an ongoing Adolescent Prospective Cohort with a follow-up of 30 years. The authors evaluated the association between pulsatile stress in childhood and adult subclinical renal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Urine measurements of creatinine and albumin were performed by an automatic biochemical analyser (Hitachi, Tokyo, Japan) in our hospital. Details of these assays were described previously 23,26 . eGFR was calculated using the formula as follows: eGFR = 175 × serum creatinine −1.234 × age −0.179 (× 0.79 for female), where serum creatinine concentration is in milligrams per deciliter and age is in years 27 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Urine measurements of creatinine and albumin were performed by an automatic biochemical analyser (Hitachi, Tokyo, Japan) in our hospital. Details of these assays were described previously 23,26 . eGFR was calculated using the formula as follows: eGFR = 175 × serum creatinine −1.234 × age −0.179 (× 0.79 for female), where serum creatinine concentration is in milligrams per deciliter and age is in years 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Details of these assays were described previously. 23 , 26 eGFR was calculated using the formula as follows: eGFR = 175 × serum creatinine −1.234 × age −0.179 (× 0.79 for female), where serum creatinine concentration is in milligrams per deciliter and age is in years. 27 UACR was calculated as urine albumin in mg divided by urine creatinine in g (mg/g).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies have confirmed that blood pressure is associated with albuminuria and increased microalbuminuria excretion in adults, which is not solely mediated through vascular damage [ 13 , 14 ]. Prospective longitudinal cohorts support the viewpoints that hypertension, and subclinical atherosclerosis in later life originate from blood pressure in childhood [ 15 , 16 ]. Moreover, longitudinal changes in blood pressure are associated with a greater risk of subclinical renal damage and CKD progression [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 95%